The Effect Of Warm Foot Sound On Blood Pressure In Pregnant Women With Essential Hypertension - Lince Palanta; Sri Dinengsih; Jenny Anna Siauta (Universitas Islam Lamongan, 2021)
Preliminary surveys at Public Health Center Watubangga for the last 3 months, namely in October-December 2020, consists of 7 working areas, 4 villages and 3 urban villages. The number of pregnant women was 157, and those experiencing essential hypertension were 15 pregnant women. This study was to determine the effect of foot soaking in warm water on blood pressure in pregnant women with essential hypertension at the Watubangga Public Health Center. This study was a quasi-experimental study design one group Pre and Post test. The study population was all normal deliveries of 138 people. The sampling technique used was total sampling with a total sample of 15 respondents of pregnant women who experienced essential hypertension. The results of statistical tests with Wilcoxon show that there is an effect of warm foot soaking on blood pressure in pregnant women with essential hypertension at the Puskesmas Watubangga with a p-value in systole (0.001), while diastole has a p-value (0.001). The conclusion is that there is Soaking feet with warm water affecting blood pressure in pregnant women with essential hypertension at the Watubangga Health Center. It is hoped that This program can be applied to clinical midwifery practice, especially for pregnant women who have hypertension and can be a reference for further research.